ChemInform Abstract: Overview of Rheological Parameters Affecting Stability of SCC. Issue 19 (18th April 2013) - Peng, Ya; Jacobsen, Stefan; De Weerdt, Klaartje; Pedersen, Bard; Marstrander, Britt Blom
Abstract Review: (SCC: self‐consolidating concrete) 28 refs.